2012
DOI: 10.1371/journal.pone.0046502
|View full text |Cite
|
Sign up to set email alerts
|

High Diabetes Prevalence among Tuberculosis Cases in Kerala, India

Abstract: BackgroundWhile diabetes mellitus (DM) is a known risk factor for tuberculosis, the prevalence among TB patients in India is unknown. Routine screening of TB patients for DM may be an opportunity for its early diagnosis and improved management and might improve TB treatment outcomes. We conducted a cross-sectional survey of TB patients registered from June–July 2011 in the state of Kerala, India, to determine the prevalence of DM.Methodology/Principal FindingsA state-wide representative sample of TB patients i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
152
12
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 164 publications
(191 citation statements)
references
References 15 publications
24
152
12
3
Order By: Relevance
“…A study conducted by Shibu Balakrishnan et al about the diabetes prevalence among Tuberculosis cases in Kerala, they got 44% of TB patients are diabetic and this was the highest reported prevalence of DM among TB patients to date. 6 In our study 11.5% and 10.7% of TB suspects got previous history of TB and family history of TB respectively. Presence of other respiratory illness (asthma, COPD.)…”
mentioning
confidence: 47%
See 1 more Smart Citation
“…A study conducted by Shibu Balakrishnan et al about the diabetes prevalence among Tuberculosis cases in Kerala, they got 44% of TB patients are diabetic and this was the highest reported prevalence of DM among TB patients to date. 6 In our study 11.5% and 10.7% of TB suspects got previous history of TB and family history of TB respectively. Presence of other respiratory illness (asthma, COPD.)…”
mentioning
confidence: 47%
“…Another studies conduted in tribal populations in Madhya Pradesh by Rao et al the prevalence of sputum positive Tuberculosis was 1518 per lakh population very high compared to present study. 6 But a study conducted in south India by Chadha et al the prevalence of sputum positive tuberculosis was 152 per positive 0.183% yes no lakh population. It is comparable with the present study.…”
Section: Sputum Positivity Among Tb Suspectsmentioning
confidence: 97%
“…A study in Kerala State in South India identified high levels of diabetes (~45%) among newly diagnosed TB patients [36]. Nearly half of these patients were not aware of their diabetic status at the time of screening.…”
Section: Contribution Of or To Policy And Practicementioning
confidence: 99%
“…Prevalence of diabetes in patients with tuberculosis from different states of India has varied from 11.6% in Punjab to 44% in Kerala [5,6]. Southern Indian states (Kerala 44%, Tamil Nadu 25%, and Pudicherry 29%) have reported higher prevalence of diabetes mellitus in such cases as compared to the Western (Ahmadabad 15%) or North Indian (Punjab 11.6%) states [5][6][7][8].…”
mentioning
confidence: 99%
“…Southern Indian states (Kerala 44%, Tamil Nadu 25%, and Pudicherry 29%) have reported higher prevalence of diabetes mellitus in such cases as compared to the Western (Ahmadabad 15%) or North Indian (Punjab 11.6%) states [5][6][7][8].…”
mentioning
confidence: 99%